Environmental Subconcussive Injury, Axonal Injury, and Chronic Traumatic Encephalopathy - Morley, Wendy A. (Frontiers in Neurology, 2018)
Brain injury occurs in two phases: the initial injury itself and a secondary cascade of precise immune-based neurochemical events. The secondary phase is typically functional in nature, and characterized by delayed axonal injury with more axonal disconnections occurring than in the initial phase. Axonal injury occurs across the spectrum of disease severity, with subconcussive injury, especially when repetitive, now considered capable of producing significant neurological damage consistent with axonal injury seen in clinically evident concussion, despite no observable symptoms. This review is the first to introduce the concept of environmental subconcussive injury (ESCI) and sets out how secondary brain damage from ESCI once past the juncture of microglial activation appears to follow the same neuron-damaging pathway as secondary brain damage from conventional brain injury. The immune response associated with ESCI is strikingly similar to that mounted after conventional concussion. Specifically, microglial activation is followed closely by glutamate and calcium flux, excitotoxicity, reactive oxygen species (ROS) and reactive nitrous species (RNS) generation, lipid peroxidation, and mitochondrial dysfunction and energy crisis. ESCI damage also occurs in two phases, with the primary damage coming from microbiome injury (due to microbiome-altering events) and secondary damage (axonal injury) from progressive secondary neurochemical events. The concept of ESCI and the underlying mechanisms have profound implications for the understanding of chronic traumatic encephalopathy (CTE) etiology because it has previously been suggested that repetitive axonal injury may be the primary CTE pathogenesis in susceptible individuals and it is best correlated with lifetime brain trauma load. Taken together, it appears that susceptibility to brain injury and downstream neurodegenerative diseases, like CTE, can be conceptualized as a continuum of brain resilience. At one end is optimal resilience, capable of launching effective responses to injury with spontaneous recovery, and at the other end is diminished resilience with a compromised ability to respond and/or heal appropriately. Modulating factors such as one’s total cumulative and synergistic brain trauma load, bioavailability of key nutrients needed for proper functioning of restorative metabolic pathways (specifically those involved in the deactivation and clearance of metabolic by-products of brain injury) are key to ultimately determining one’s brain resilience.